2018
DOI: 10.4103/jlp.jlp_136_17
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis area: A new parameter of erythrocyte osmotic fragility for screening of thalassemia trait

Abstract: BACKGROUND: One-tube osmotic fragility test (OFT) is widely used for screening thalassemia traits. Interobserver variation may occur with 0.36% NaCl-based OFT due to the naked eye result reading style. PURPOSE: The purpose of this study was to establish and evaluate the novel numerical OFT-based parameter, so-called hemolysis area (HA), in screening thalassemia traits. MATERIALS AND METHODS: The portable spectrophotometer was invented capable of calculating the HA values. The HA values were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In addition, a number of novel GWA significant variations were found in metabolic enzymes (Hexokinase 1 -HK1; p<4.90E-11), stress kinases (MAPKAPK5; p<2.24E-13), ion channels (Piezo type mechanosensitive ion channel component 1; PIEZO1; p<4.04E-14), and other proteins, such as Myosin IXB (MYO9B; p<9.88E-15). Supporting the internal validity of these findings, many of these SNPs are in proteins known to cause RBC disorders such as spherocytosis (23), elliptocytosis (29), xerocytosis (30), and alpha-thalassemia (31).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, a number of novel GWA significant variations were found in metabolic enzymes (Hexokinase 1 -HK1; p<4.90E-11), stress kinases (MAPKAPK5; p<2.24E-13), ion channels (Piezo type mechanosensitive ion channel component 1; PIEZO1; p<4.04E-14), and other proteins, such as Myosin IXB (MYO9B; p<9.88E-15). Supporting the internal validity of these findings, many of these SNPs are in proteins known to cause RBC disorders such as spherocytosis (23), elliptocytosis (29), xerocytosis (30), and alpha-thalassemia (31).…”
Section: Introductionmentioning
confidence: 66%
“…We identified twenty loci that were genome-wide significant in all sample analysis (p<5x10 -8 ) for at least one of the hemolysis measures (Table 1). Many of the identified variants were concentrated in proteins known to cause human RBC disorders characterized RBC fragility such as dehydrated hereditary stomatocytosis (PIEZO1) (41,42), spherocytosis ANK1, SPTA1, SLC4A1 (23,43), ellipto-poikilocytosis (SPTA1) (44), xerocytosis (PIEZO1) (30), alpha-thalassemia (HBB) (31), and spontaneous and oxidant stress-induced hemolytic anemia (HK1 and G6PD) (16,45). Providing additional validity, many of the implicated SNPs have been associated with laboratory complete blood cell count measurements, such as reticulocyte counts (SPTA1 and PIEZO1) (46), and other complete blood count indices (G6PD) (47).…”
Section: Discussionmentioning
confidence: 99%
“…The hemolysis area of normal individuals was 67.1 ± 12.6 units. In contrast, the hemolysis area of HbE carriers, β-thalassemia carriers were found to be 36.4 ± 13.9, 18.6 ± 1.1, respectively [54].…”
Section: 45% Nacl In Glycerine or Glycerine Saline Solution (Gss)-bmentioning
confidence: 80%
“…The β-thalassemia carriers all have the positive OFT results, while HbE carriers have either positive, negative, and suspicious OFT results (see the text for detail). Laboratory Diagnosis of β-Thalassemia and HbE DOI: http://dx.doi.org/10.5772/intechopen.90317cuvette[54]. To perform this test, 20 μL of EDTA blood is mixed with 5 mL of GSS in 12 × 75 polypropylene cuvette.…”
mentioning
confidence: 99%
“…EOF is a measurement of the resistance of erythrocytes to hypotonic solutions and hemolysis, which primarily depends on the surface area/volume ratio in erythrocytes. Clinically, EOF can be applied to screening and evaluating certain hemolytic diseases, such as thalassemia, hereditary spherocytosis, and glucose-6-phosphate dehydrogenase deficiency ( Emilse et al, 2018 ; Tatu and Sweatman, 2018 ). Routine blood tests showed that the average erythrocyte volume in HAPC rats had increased, leading to a relative decrease in the surface area/volume ratio of erythrocytes, which may increase osmotic fragility.…”
Section: Resultsmentioning
confidence: 99%